Demography of owned dogs across an East African continuum of high-low human density - Murungi, Maurice K.; Thomas, Lian F.; Bor, Nicholas; Masaku, Ian; Anyango, Mercy; Munywoki, Peterkin N.; Glazer, Camille; Muloi, Dishon M.; Fèvre, Eric M. (Elsevier, 2025)
Understanding the demographics of domestic dogs is essential for effective disease control strategies, particularly in areas where dogs are key reservoirs of diseases such as rabies. In this study, conducted in a region proximate to Nairobi, Kenya, we aimed to address the lack of current data on dog demographics. This area spans a high-to-low human density continuum, providing a unique setting for examining the relationship between human and dog populations.